Profile of the Pediatric Infectious Disease Workforce in 2015. (22nd December 2017) - Yeh, Sylvia H; Vijayan, Vini; Hahn, Andrea; Ruch-Ross, Holly; Kirkwood, Suzanne; Phillips, Terri Christene; Harrison, Christopher J
Abstract : We performed a survey of board-eligible/board-certified pediatric infectious disease specialists regarding their current demographics, work scope, and job satisfaction to identify potential trends in projecting the future of the pediatric infectious disease job market. Abstract: Background: Almost 20 years have elapsed since the last workforce survey of pediatric infectious disease (PID) subspecialists was conducted in 1997–1998. The American Academy of Pediatrics Section on Infectious Diseases in collaboration with the Pediatric Infectious Diseases Society sought to assess the status of the current PID workforce. Methods: A Web-based survey conducted in 2015 collected data on demographics, practice patterns, and job satisfaction among the PID workforce, and identified factors related to job placement among recent fellowship graduates. Results: Of 946 respondents (48% response rate), 50% were female. The average age was 51 years (range, 29–88 years); 63% were employed by an academic center/hospital, and 85% provided direct patient care; and 18% were not current PID practitioners. Of the 138 (21%) respondents who had completed a PID fellowship within the previous 5 years, 83% applied for <5 PID positions; 43% reported that their first position was created specifically for them; 47% had 1 job offer, and 41% had 2 or 3 job offers; 82% were employed within 6 months; and 74% remained at the institution of their first job. Respondents who were practicing PID full-time or part-time (n = 778) indicated desiring more focused training in immunodeficiencies (31%), transplant-related care (31%), and travel/tropical medicine (28%). Overall, 70% of the respondents would "definitely" or "probably" choose PID again. Conclusions: Most respondents were satisfied with their career choice in PID. Most of the recent fellowship graduates were employed within 6 months after training. We identified potential areas in which the PID community can focus efforts to maintain the pipeline and improve satisfaction among its physicians.